Improving Rural Access to Care: Recommendations for Georgia's Health Care Safety Net - Karen Minyard; Chris Parker; John Butts (Georgia Southern University, 2016)
Background: In Georgia, the safety net provides health care services to vulnerable populations scattered across 74 urban and 85 rural counties. In rural communities, the safety net is challenged with longstanding gaps in service provision and persistent difficulty in making services accessible. The rural safety net in Georgia is vulnerable. Methods: An environmental scan was conducted of the Georgia rural safety net to assess who it serves, its providers, and how care is accessed in light of the Affordable Care Act (ACA). The scan included analysis of population-based census and health databases and a literature review to inform recommendations. Results: The population served by the rural safety net is typically older, poorer, and less healthy than the population in urban areas. The principal providers of care in the rural safety net are community hospitals, federally sponsored and free or charitable clinics, and some health departments. While the ACA provides an opportunity to increase insurance coverage and access to care, it poses a financial challenge to providers of the rural health safety net. As the health system evolves, the rural health safety net must adapt to shifting priorities and patient populations. Conclusions: To enhance the sustainability of the rural safety net, it is necessary for providers to focus on coordination of care through integration of services and broader health system partnerships. Providers of the Georgia rural safety net and stakeholders should focus on (a) ensuring a comprehensive assessment of all components of the safety net, (b) facilitating change through high-performing health departments and community-based organizations, (c) funding efforts to provide patient-centered medical homes for the rural uninsured, (d) emphasizing the value of technology in the provision of care and information/data exchange, and (e) rewarding innovations in rural and safety net workforce development and deployment.